The moral laboratory : experiments examining the effects of reading literature on social perception and moral self-concept - Hakemulder, Jèmeljan, 1966- (Utrecht publications in general and comparative literature, 2000)
The idea that reading literature changes the reader seems as old as literature itself. Through the ages philosophers, writers, and literary scholars have suggested it affects norms, empathic ability, self-concept, beliefs, etc. This book examines what we actually know about these effects. And it finds strong evidence for the old claims. However, it remains unclear what aspects of the reading experience are responsible for these effects. Applying methods of the social sciences to this particular problem of literary theory, this book presents a psychological explanation based upon the conception.